2016
DOI: 10.1177/0955749016649107
|View full text |Cite
|
Sign up to set email alerts
|

Fifty years of Tanzania’s national/public library service

Abstract: National cum public library services were set up in Tanzania and in a number of other African countries just before or shortly after independence. In addition to being the national public library service, the Tanzania Library Services Board (TLSB) is a legal deposit library and produces the national bibliography. Starting from virtually nothing, TLSB was operating purpose-built libraries in the main urban centres by the mid-1970s. It received much support from the Tanzanian government and from foreign donors u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The evolution of e-book technology could address these challenges by providing a more versatile and flexible mechanism for learners to access and use library resources. A study conducted by Mcharazo and Olden (2016) recommends the use of electronic resources in libraries to enhance efficiency and effectiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The evolution of e-book technology could address these challenges by providing a more versatile and flexible mechanism for learners to access and use library resources. A study conducted by Mcharazo and Olden (2016) recommends the use of electronic resources in libraries to enhance efficiency and effectiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, printed books may be misplaced, degrade or otherwise lost or stolen, which may requires the library to purchase new copies of the same book (Anuradha & Usha, 2006;Roesnita & Zainab, 2013). This tends to be difficult since most libraries have limited financial resources (Burnett, 2013;Mcharazo & Olden, 2016). The evolution of e-book technology could address these challenges by providing a more versatile and flexible mechanism for learners to access and use library resources.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ideally, libraries should always provide and improve good service and provide convenience for visitors. The library users will be happy to come to the library if the library staff serve with a warm welcome, provide instructions patiently, friendly, and sensitive to the needs of its users (2,3). All of this can be realized if all aspects in the library support each other and work in harmony, harmony, and balance.…”
Section: Introductionmentioning
confidence: 99%
“…In Tanzania, LIS education began in 1972 at the elementary certificate level under the Tanzania Library Service Board located in Dar es Salaam. The LIS diploma qualification was introduced in 1989 at the School of Library, Archives and Documentation Studies (SLADS) found in Bagamoyo, Pwani region (Mcharazo andOlden 2016, Manda 2006: 2). The University of Dar es Salaam introduced a master's programme in LIS in 1997 and a PhD programme in 2000.…”
Section: Introductionmentioning
confidence: 99%